DETERMINANT IN ACCEPTANCE OF CASHLESS PAYMENT: AN EMPIRICAL STUDY IN MALAYSIA - Ishak, Izzaamirah (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the factors that may have influence to the acceptance of cashless payment. A survey method was employed using a sample of 204respondents.The objectives of this research are to determine the determinant of cashless payment among Malaysian, and to evaluate the impact of determinant in acceptance of cashless payment. There are 4 factors; trust, perceived usefulness, perceived ease of use and risk. A quantitative study has been conducted for this research with questionnaire as data collection. The research used multiple regression analysis to recognize the impact that are related to acceptance of cashless payment. The findings of this study reveals there is a positive impact of trust, perceived usefulness, and perceived ease of use towards acceptance of cashless payment, whereas risk has a negative impact. This findings would help to determine whether Malaysian societies are heading towards cashless society in year 2050.